Oxygen isotope analysis of the eyes of pelagic trilobites: Testing the application of sea temperature proxies for the Ordovician - Bennett, Carys E.; Williams, Mark; Leng, Melanie J.; Lee, Martin R.; Bonifacie, Magali; Calmels, Damien; Fortey, Richard A.; Laurie, John R.; Owen, Alan W.; Page, Alex A.; Munnecke, Axel; Vandenbroucke, Thijs R.A. (Elsevier, 2018)
The oxygen isotope composition of well-preserved trilobite eye calcite, retaining its original optical properties, represents a possible source of information on Paleozoic sea temperatures. Species of the epipelagic telephinid genera Carolinites and Opipeuterella from strata of Early to Middle Ordovician age in Spitsbergen and Australia were analyzed, and compared with benthic asaphid species. Scanning electron microscope (SEM), cathodoluminescence (CL), electron microprobe and Electron Backscatter Diffraction (EBSD) techniques were used to assess eye preservation prior to isotope analysis. Some apparently well-preserved eyes are identified from the Valhallfonna (Spitsbergen) and Emanuel (Australia) formations. The eyes show a wide variation in δ18O values: −6.2‰ to −9.8‰ for the Valhallfonna Formation, −3.2‰ to −10.4‰ for the Emanuel Formation, and −3.6‰ to −7.4‰ for the Horn Valley Siltstone (Australia). Intra-eye Secondary Ion Mass Spectrometry (SIMS) isotope results reveal an even larger range in δ18O in some specimens (δ18O of −2.4‰ to −10.4‰), suggesting that the trilobite eyes have undergone cryptic recrystallization. A sub-set of trilobite cuticle from the three formations were analyzed for their carbonate clumped isotope compositions (Δ47), and yielded crystallization temperatures above 50 °C, consistent with diagenetic alteration. The SIMS and Δ47 results suggest that classic preservation assessment protocols for the stable isotope study of deep-time carbonate samples may be insufficient, especially for these techniques. There is a need for extensive microstructural characterization of lower Paleozoic biogenic carbonates, by techniques including EBSD, SIMS and Δ47, before their stable isotope signatures can be used with certainty in paleoclimate studies.